Prospective evaluation of serum biomarker levels and cartilage repair by autologous chondrocyte transplantation and subchondral drilling in a canine model - Korakot Nganvongpanit (2018)
Introduction: The purpose of this study was to evaluate serum chondroitin sulfate (CS) and hyaluronic acid (HA) levels and the capability of cartilage repair of full-thickness cartilage defects after treatment with two different fundamental surgical techniques: autologous chondrocyte transplantation (AC) and subchondral drilling (SD). Methods: A 4-mm-diameter full-thickness cartilage defect was created in each of 10 skeletally mature male outbred dogs. The dogs were randomly separated into two groups. Groups A and B were treated with AC and SD, respectively. An evaluation was made at the 24th week of the experiment. Serum was analyzed prospectively - preoperatively and at 6-week intervals - for CS and HA levels by enzyme-linked immunosorbent assay (ELISA) and ELISA-based assays, respectively. Results: The cartilage repair assessment score (median ± standard deviation) of group A (9.5 ± 2.5) was significantly higher than that of group B (2.5 ± 1.3) (P < 0.05). Group A also demonstrated a better quality of hyaline-like cartilage repair. Prospective analysis of serum WF6 and HA levels between the two groups did not show any significant difference. Serum WF6 levels at the 24th week of the experiment had a negative correlation (r = -0.69, P < 0.05) with the cartilage repair assessment score, whereas serum HA levels tended to correlate positively (r = 0.46, 0.1 < P < 0.05). Conclusions: AC treatment provides superior results to SD treatment, according to morphology, histology, and cartilage marker levels. AC treatment demonstrated a smoother surface, less fissure, better border integration, and a more reliable outcome of repairing cartilage. Moreover, a decreasing level of serum WF6, which correlated with good quality of the repairing tissue at the end of the follow-up period, was found predominantly in the AC group. Serum WF6 therefore should be further explored as a sensitive marker for the noninvasive therapeutic evaluation of cartilage repair procedures. © 2009 Nganvongpanit et al.; licensee BioMed Central Ltd.